Zur Geschichte der schweizerischen Raumplanung. - Lendi, Martin (TH Zürich, NSL, 2006)
Die Geschichte der schweizerischen Raumplanung hat ihren institutionellen Höhepunkt mit dem Erlass des Verfassungsartikels über die Raumplanung im Jahre 1969 und mit jenem des Bundesgesetzes von 1979 erlebt. Bevor der Beitrag auf die Raumplanung als dauernde, alle raumwirksame Bereiche umfassende Aufgabe, auf die Menschen, Ideen, Erfolge und Misserfolge eingeht, spürt er den Wurzeln des schweizerischen raumplanerischen Denkens nach. Diese reichen weit zurück, besondere Einschnitte stellen dabei die Jahre 1848/1874 durch die Etablierung des liberalen, föderativen und sozialen Rechtsstaat dar und die Entwicklung der materiellen Kernideen rund um die Landesausstellung im Jahre 1939. goj/difu

Though the history of Swiss spatial planning can be traced back to the Middle Ages, when it already reflected economic interests, power structures and socio-cultural conditions, it was the social, political and economic developments of the 19th century that furnished core ideas that can still be felt today. The legislative basis laid in 1969 was an institutional milestone in the autonomy of this field. However, since then the changes and challenges in mobility, urbanization with concomitant concerns for rural areas, increasing population and its demands on living space, and concerns for the natural environment, along with scientific developments and economic internationalization, have brought about a need for a new orientation, new strategies, new tools and creative measures. Spatial planning now has to prove its ability to not only solve current problems, but to anticipate the future. difu
Keywords: Raumplanung; Raumordnung; Geschichte; Verfassung; Leitbild; Raumordnungsrecht